PENGARUH SENAM LANSIA TERHADAP KUALITAS TIDUR PADA LANSIA DI PELAYANAN SOSIAL TRESNA WERDHA KHUSNUL KHOTIMAH KELURAHAN SIMPANG TIGA PEKANBARU TAHUN 2016 - Nislawaty Nislawaty (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2017)
Factors that affect the quality of sleep in the elderly include illness, depression, environment, lifestyle, and sleep disorders. Physical training or certain sports can be useful to overcome sleep disorder needs. Elderly gymnastics is a mild exercise that is easy to do is not burdensome, which can be applied to the elderly. This study aims to determine the influence of elderly gymnastics on sleep quality in the elderly in Panti Sosial Tresna Werdha Khusnul Khotimah. The research design used was Quasi Eksperimen with One Group Pretest Posttest design. The sample in this study is as many as 24 elderly who experience sleep disorder. The results showed that the quality of sleep in the elderly before the elderly gymnastics most entered the category of poor sleep quality (100%). After doing elderly gymnastics, poor sleep quality becomes good sleep quality that is (45,8%). From the result of statistical test result for t table equal to 2,080. The value of t arithmetic> t table (24,763> 2,080) and the significance value (sig 2 tailed) of 0.000 (less than 0.05). The conclusion of this research is there is influence of elderly gymnastics toward sleep quality at elderly in Panti Sosial Tresna Werdha Khusnul Khotimah Pekanbaru. Elderly gymnastics very useful in improving sleep quality at elderly so expected in elderly to be able to increase importance of consciousness of elderly gymnastics